KNOWLEDGE ABOUT STORAGE OF SYRUP DRUG ON PATIENT IN PUSKESMAS PEKANBARU CITY - Desmariani -; Fintolin Jaya Putri; Seftika Sari; Ratna Sari Dewi; Adriani Susanty; Enda Mora (Universitas Muhammadiyah Magelang, 2021)
Drug storage is something that must be considered because it can affect the quality of the drug. Storage conditions must adapt to the stability of each drug. This study aims to determine the level of knowledge about the storage of syrup drug preparations in patients in all public health centers in Pekanbaru. The research method is analytic observational with cross sectional design. The research sample was the people who visited all health centers in Pekanbaru city which were selected by purposive sampling technique according to the inclusion and exclusion criteria and obtained a sample of 160 respondents. The instrument is a knowledge questionnaire that has been tested for validation and reliability. The knowledge questionnaire contained 14 valid questions (r=0.818). Presentation of data with bar charts and narrative text. The results of the study revealed that there were 66 respondents (41.25%) in the good knowledge category and 94 respondents (58.75%) in the sufficient knowledge category and none of the respondents had less knowledge in the category. From these results, it can be concluded that most people do not know well how to store syrup drugs, so it is necessary for the role of pharmacists to provide education to the public, especially regarding how to store drugs correctly